Training inpatient psychiatric nurses and staff to utilize CBTp informed skills in an acute inpatient psychiatric setting. Issue 1 (2nd January 2022) - Eisen, Katherine; Kharrazi, Neda; Simonson, Alix; Lean, Melanie; Hardy, Kate
ABSTRACT: Background: The aim of this study was to investigate the impact of a novel, brief CBTp-informed skills training, called Positive Practices for working with Psychosis (PPP), on recovery-orientation of frontline inpatient psychiatric staff, and on staff knowledge of and confidence using skills informed by Cognitive Behavior Therapy for psychosis. Methods: Twenty five providers participated in 12 hours of PPP training. We examined changes in providers' skills in delivering recovery-oriented care (focusing on skills advocacy, evidence based practice, stigma, optimism, and client preference), and providers' knowledge of, and confidence in using CBTp informed skills, using the Competency Assessment Instrument (CAI) and the Knowledge and Confidence Using CBTp Skills Scale (KC-CBTp). Results: were analyzed using paired-sample t-tests. Results: Significant gains (p < .001) in self-rated knowledge and confidence using CBTp skills were seen on 8 of 9 domains measured. On the CAI, significant gain in optimism was seen (p = .004). Discussion: Brief CBTp informed PPP training is a potential intervention for frontline staff, associated with significant gains in knowledge of, and confidence in using, evidence based CBTp-informed skills, and increased optimism in attitudes towards recovery. Limited change on recovery based competencies of staff was seen in other domains and requires further investigation.